First record of the genus Bezzia in Chile, with a description of a new species of the venustula group (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2001)
A new species of ceratopogonid diptera from Central Chile, Bezzia chilensis, is described and illustrated based on an adult male and five female specimens, and also the widespread species Bezzia nobilis (Winnertz) is firstly recorded for the country.